PRACTICAL APPLICATION OF KNOWLEDGE MANAGEMENT MODELS: ASSESSING EXISTING KM MODELS FROM THE PERSPECTIVE OF PRIVATE HOSPITALS OF NORTH EAST INDIA - Pradyut Kumar Borah; Biswa Ranjan Phukan; Sanjib Raj (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
With the growing importance attached to knowledge management (KM), researches on various KM implementation options have come up which resulted in enunciation of several models and frameworks for KM. These are considered from the practical perspectives underlying the need for some organising principles forming a general framework which identifies and categorise different activities in KM process. The Models in KM shows a process that helps organizations to use a more collective and systematic process of data mining, data capture, storage, refinement, codification, utilization, updation and utilization to enhance organizational effectiveness. This research endeavours to look into practical application of the KM models and how far these are being applied. The objective of the research is to look into the practical application of knowledge management models from the perspective of private hospitals in Northeast India. The objective is to see how the different KM models can be applied in the sector for performance enhancement and how these models fit in to the actual practices required in the hospitals For this the KM process in the hospitals have been studied through a primary survey and attempt was made to relate these activities to the components of the KM models considered for this research. As far as the practical application of KM models is concerned, adoption of particular model is not noticed though various components of the models under study are being practiced. It is seen that components of each of the models are significant for the healthcare sector, however a single model is not being practically applied and activities that conforms to all the models under study are being practiced. It is envisaged that the findings would give an insight into the practical applications of KM models from the perspective of the healthcare sector.